Retrospective study of clinical characteristics and viral etiologies of patients with viral pneumonia in Beijing. (May 2021) - Zhao, Xiang; Meng, Yao; Li, Duo; Feng, Zhaomin; Huang, Weijuan; Li, Xiyan; Wei, Hejiang; Zeng, Xiaoxu; Wang, Dayan
Aims: The virus is common in patients with viral pneumonia. However, the viral etiology and clinical features of patients with viral pneumonia in China remain unclear. The main purpose of this study was to analyze the viral causes and epidemiology of patients with viral pneumonia in Beijing, which can significantly improve the pertinence and accuracy of clinical treatment of the disease. Methods: Firstly, 1539 respiratory specimens of pneumonia (oropharyngeal swabs, nasopharyngeal swabs, saliva samples and bronchoalveolar lavage fluid) were collected from 19 hospitals in Beijing from September 2015 to August 2018. Then, TaqMan low-density microfluidic chip technology was used to detect viral pneumonia specimens in 1539 respiratory tract specimens of pneumonia and determine the types of viral bacteria in them. Lastly, the analysis of demographic, clinical and etiological data of patients with viral pneumonia was performed. Results: The results showed that among the 1539 respiratory tract specimens with pneumonia, 760 were detected as viral pneumonia specimens, with a positive rate of 49.4%. Among which, 467 were infected with mono-viral and 293 were infected with multi-viral. Influenza A virus (Flu A), mycoplasma pneumoniae (MPn), Ebola virus (EBV) and herpes simplex virus type 1 (HSV-1) were the major viral components in the samples of these patients. Furthermore, these viral species were significantly associated with sample sources, onset season and certain clinical characteristics. Discussion: Our findings may provide corresponding treatment strategies for viral pneumonia patients infected with specific viruses.